Barbados, the favoured favourite? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Barbados, the favoured favourite?Barbados is often quoted as a success story within the ACP Group. Its economy is based essentially on sugar and tourism. The importance given to education lies behind its success. It has long been a feature of...